I sleep in my kitchen : comfort food recipes from my Palestinian American home - Daud, Mariam; Timberlake, Emily (Clarkson Potter/Publishers, 2026)
"From the creator of the popular social media account Mxriyum comes 100 recipes that blend Palestinian heritage with creative twists, offering approachable and flavorful dishes for home cooks and bakers of all skill levels. Mariam Daud is a Palestinian American home cook who posts mouthwatering meals with distinctly elegant presentations on social media. In I Sleep in My Kitchen, Mariam shares her most beloved dishes, a collection of comforting recipes that reflect her heritage as well as showcase her creativity in the kitchen. Mariam offers readers a taste of traditional Palestinian cuisine with cherished family recipes for the dishes she grew up eating. You'll find a celebratory Msakhan, the national dish of Palestine, made with freshly baked flatbread topped with heaps of caramelized onions, succulent stewed chicken, fresh parsley, and toasted pine nuts. Mariam also includes personal favorites from her childhood, like her mother's irresistible Cheese Fatayer, a savory cheese-stuffed pastry that was a household staple on weekend mornings. Throughout, you'll find familiar dishes infused with Middle Eastern flavors, like a Mediterranean Pasta Salad with Sumac-Vinaigrette and a Tahini and Browned Butter Banana Bread. I Sleep in My Kitchen highlights some of Mariam's most popular recipes, like her tender, pull-apart Cinnamon Rolls and her Triple Stack Smash Burgers, alongside a wide range of brand-new creations, from Bang Bang Shrimp Tacos with Cabbage Slaw and Fluffy Browned Butter Rolls with Flaky Sea Salt to a Loaded Chickpea Salad with Bulgur. Readers will find flavorful recipes for breakfasts, small plates, salads, soups, and mains in addition to Mariam's signature sweet and savory baked goods. With her simple and satisfying recipes, I Sleep in My Kitchen is a celebration of food, family, and the joy of cooking"-- Provided by publisher.